Phytoplankton dynamics and bloom formation in the oligotrophic Eastern Mediterranean: Field studies in the Aegean, Levantine and Ionian seas. (January 2020) - Varkitzi, I.; Psarra, S.; Assimakopoulou, G.; Pavlidou, A.; Krasakopoulou, E.; Velaoras, D.; Papathanassiou, E.; Pagou, K.
Abstract: This study attempts to elucidate the dynamics of phytoplankton biomass (as Chl- a ), productivity, community structure and bloom formation in different regions of the oligotrophic Eastern Mediterranean (EMed). With this scope, several chemical and phytoplankton parameters were studied along a transect of 1300 km across different pelagic environments from North (N) Aegean to South (S) Aegean, Levantine and Ionian seas during spring and summer 2008. An exceptional spring phytoplankton bloom was detected in the S Aegean Sea, dominated by large sized diatoms and spreading almost throughout the euphotic zone. This unprecedented bloom was triggered by the nutrient enrichment of surface water masses due to cyclonic formations and a strong convection event that caused deep mixing. There was a clear decreasing trend of phytoplankton biomass and productivity from the Aegean towards the Levantine and Ionian seas. The same trend was recorded for N:P ratios and increasing P limitation from the Aegean to the Levantine and Ionian seas. Si:N ratio indicated an overall deficiency of N in relation to the available Si. Picoplankton was the dominant and most productive size fraction, except for the S Aegean in spring due to the diatom bloom. Chl- a maxima in the N Aegean were constrained within the surface layer occupied by modified Black Sea water, deepening progressively towards the Levantine and Ionian seas, especially during the stratified period. Nanoflagellates and small-sized dinoflagellates were important phytoplankton components in the N Aegean inter-seasonally, whereas in the S Aegean the large diatoms associated with the spring blooming shifted to nanoflagellates and small dinoflagellates in the stratified period. Coccolithophores and small diatoms were significant components in the Levantine and Ionian seas, whereas the overall microplankton community structure did not demonstrate prominent seasonal patterns. These results confirm that oligotrophy is the main driving force for the distribution of phytoplankters, but also offer evidence of how the low nutrient-low chlorophyll EMed system can occasionally support high phytoplankton biomass and generate prominent blooms. This work will help elucidate the structure and functioning of EMed pelagic food webs and contribute to the analysis of signals related to structural and functional ecosystem changes.